Philosophy of education: meaning, updating and poietica education at the intersection between the subject, audiovisual media and technologies: Philosophy of education: meaning, updating and poietica education at the intersection between the subject, audiovisual media and technologies - PALLARÈS PIQUER, Marc (Utopía y Praxis Latinoamericana, 2023)
This work addresses the role of the philosophy of education in the current panorama, marked by the technological-digital galaxy. It is explained that the philosophy of education complements pedagogy and presents frameworks for reflection that, based on a conception of the politics as the axis of concern and reproduction of doing in itself and from poietica education, which is what makes the existence something beautiful and valuable in itself, you can lay the foundations to conceive the education as an action at the service of optimizing humanity.